Abrasive wear-resistance of composite materials and coatings on titanium-chromium diboride based. - Коновал, В.П. (Problems of Tribology, 2015)
Konoval V. P. Abrasive wear-resistance of composite materials and coatings on titanium-chromium diboride based.Composites of TiCrB2–(NiAlCr) systems with different ratio of refractory and metal phase have been produced by sintering. The coatings on the base of TiCrB2–(NiAlCr) composites were electrospark method deposited on 65G steel. The structure, mechanical and tribotechnical properties of the composites and coatings have been studied. The obtained composites have heterophase fine structure with uniform phase distribution, high hardness (HV11–23 GPa) and wear-resistance under abrasive wear conditions. It was determined that wear-resistance of coatings is 30 to 60 % lower than of the initial compact material. It is due to that the coatings have been lower hardness (HV9–17 GPa). This results from the formation of ultrafine coating microstructure and partial mixing of the coating and substrate materials. The wear resistance of the composites and coatings improves with a higher amount of the refractory phase in their composition. In general, the wear rates are quite low and testify that composite materials and electrospark-deposited coatings which consist over 50 % of refractory phase are suitable for the operating under abrasive wear conditions at loads up to 2 MPa.